UH-60A rotor and coupled rotor-fuselage simulation framework validation and analysis - Rex, W.; Pflumm, T.; Hajek, M. (My University, 2019)
In helicopter engineering advanced simulation means are available today which allow to run analysis and optimization tasks using modern computational capabilities [1-7]. In this context it is important to demonstrate the validity of the simulation model and the simulation approach by comparison with experimental data. This work establishes a validated reference model similar to the UH-60A for research activities on rotor blade design and analysis of rotor-fuselage coupling mechanisms. The focus is on structural representation. Literature is reviewed for data to define and validate the model. Main rotor performance and structural characteristics are in good agreement with the experimental data. Two independently established modal fuselage representations are mutually consistent and agree with literature at lower but not at higher frequencies. Coupled rotor-fuselage simulations show reasonable results compared to test data. However, the approach does not represent experimental mean half peak-to-peak hub accelerations exactly.